Soft tissue changes in relationship to movement of hard structures in bimaxillary surgery, eighteen months follow up - Francisco L. Duque-Serna; Pedro M. Jaramillo-Vallejo; María Isabel Calderón-Tangarife; Juan David Arango-Uribe (Universidad de Antioquia, 2009)
Introduction: the purpose of this study was to evaluate the long term follow up of soft tissues to hard tissues after bimaxillary orthognathic surgery with or without mentoplasty Methods: twenty two patients treated at the Hospital Universitario San Vicente de Paul (HUSVP) during years 2004 to 2006. Two radiographs were taken: pre-surgery (T1) one month before surgery and post-surgery (T2) eighteen months after the procedure. Results: it was found in this study that in the horizontal maxillary plane, upper labralis had the highest follow up with 95 %, followed by subnasal and nasal tip with 67 and 60% respectively. In the mandible the results were 111%, 81.9, 69, 68 and 30% for inferior labralis, Point B, menton, pogonion and gnation respectively; In the vertical plane the follow up was 112, 100 and 55% for upper labralis, nasal tip and subnasal respectively. The mandible showed a follow up of 92% for menton, 72 for gnathion, 54 for pogonion and 32 for Point B in relationship with their corresponding hard tissue points. When we compared the differences of follow up of soft tissues in relation with the hard tissues in the horizontal plane in patients with and without mentoplasty,a statistically significative difference was found for point B and Pogonion: in the vertical plane the difference was significant for Gnation, Point B and pogonion. Conclusions: it is concluded that the follow up of soft tissues to hard tissues after orthognathic bimaxillary surgery eighteen months later is different to uni-maxillary surgery and new parameters must be established for the Latin American population.